An unquiet peace - Steinberg, Shaina (Bishop & Gallagher mystery, 2025)
"Mr. and Mrs. Smith meets Code Name Verity in this propulsive, quick-witted mystery set in late-1940s Los Angeles, as former WWII spyEvelyn Bishop and LA noir detective Nick Gallagher team up as an unconventional duo..."--Provided by publisher.